FAITHFUL TRANSLATION ON IJEN GEOPARK INFORMATION BOARD FROM ENGLISH INTO INDONESIAN: A TRANSLATION STUDY - Michelle Jacqueline Doloksaribu; Ni Made Diana Erfiani (LPPM Universitas Dhyana Pura, 2023)
This research aims to analyze the usage of faithful translation procedures employedin converting a tourism information board from English to Bahasa Indonesia. Thedata source was an information board on Ijen Geopark located in Bondowongso,which was collected using a cellphone by capturing a photograph of its content in theboard. The study employs a qualitative descriptive approach to collect and analyzedata from the board content. Newmark's theory (1988) on faithful translation servesas the framework for analyzing the gathered data. This approach prioritizesmaintaining the accuracy of the content, style, tone, and cultural nuances of thesource text. While allowing for some linguistic adjustments to ensure readability andnatural flow in the target language. The analysis revealed that the content in theinformation board with a total of 82 data collected was using faithful translationtechniques when translating from the target language to the source language in thisparticular information board which still captured the essence and integrity of theoriginal work without altering its fundamental message or context.